Some Computer Applications to Problems in Human Genetics - Mckusick, V. A. (Methods of Information in Medicine, 1965)
Computer methods have been useful in the following applications in human genetics research (among many): 1) demonstration of what genes are on the same chromosome and the distance separating pairs of loci on the chromosome; 2) demonitration of sex differences in the recombination fraction; 3) assemblage of catalogs of rare recessive phenotypes in man; 4) maintenance of total genealogy of closed populations for such uses as a) determining common ancestor(s) of parents of persons with rare recessive disorders, and b) calculation of coefficients of consanguinity.